KAPABILITAS ORGANISASI DALAM PENGELOLAAN BADAN USAHA MILIK DESA DI DESA NGASO KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU TAHUN 2023 - Andini, Aura Fatikha; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The role of village government in mobilizing community participation towards welfare is persuasive in planning, creating, and improving community capacity in using resources or potentials, both Human Resources and Natural Resources, which successfully improve the welfare of village communities in managing village finances or village funds, implementation, development, village community development to create order, harmony, security, and empowerment in village communities. In the effective management of Village-Owned Enterprises, laws and government regulations serve as a reference for maintaining the sustainability of these enterprises, ensuring they remain optimal. This study employs a descriptive qualitative approach to gain an in-depth understanding of the real-world conditions in the field. The data collection techniques employed include in-depth interviews with Village-Owned Enterprise managers, direct observation of operational activities, and documentation studies related to regulations and financial reports. The collected data were analyzed using thematic analysis techniques to identify important patterns related to organizational capabilities. The results of the study indicate that the organizational capabilities of the Ngaso Mandiri Village-Owned Enterprise still face various challenges in four main aspects. In terms of knowledge and skills, managers do not fully understand regulations, financial accounting, risk management, and recording technology, which results in administrative errors and low efficiency. In terms of technical systems, although SOPs have been prepared, their implementation has not been optimal due to weak supervision and the use of a manual recording system that is prone to errors. The managerial system aspect shows income instability weak internal coordination and a lack of strong leadership, although there have been efforts to improve through limited digitalization. Meanwhile, in terms of values and norms, transparency and accountability have not been fully achieved due to limited data access and suboptimal real-time reporting, although there is a strong commitment to the values of honesty and cooperation. Keywords: Organizational Capability, Management BUMDes